'Help, not punishment': Moving on from physical punishment of children. (14th April 2015) - Porzig-Drummond, Renata
<x content-type="archive" xml:space="preserve">Abstract</x> Although the physical punishment of children is overall an ineffective disciplining strategy, has adverse long-term psychological effects, and carries the risk of physical punishment escalating into child abuse, parental physical punishment is lawful in all Australian states and territories within the bounds of lawful correction or reasonable chastisement. What is considered to be reasonable is open to considerable interpretation, which further increases the risk of physical harm to children. Physical punishment of children also contravenes the United Nations Convention on the Rights of the Child, which Australia has ratified. Although more effective disciplining strategies, such as cognitive-behavioural parenting strategies, are available and have been advocated by professional organisations, the vast majority of Australian parents condone parental physical punishment of children and are opposed to its prohibition. Predictors for this stance include perceived social norms, the belief that physically punishing children is an effective disciplining strategy and a parent's right, a perceived absence of alternative parenting strategies, and fear of prosecution if physical punishment were to be banned. Countries that have phased out the physical punishment of children have demonstrated that, to encourage a shift in parental attitudes and behaviours, public awareness about the detrimental effects of physical punishment and the effectiveness of alternative disciplining strategies needs to be raised. Additionally, parents require support through free and convenient access to evidence-based parenting programmes that promote alternative disciplining strategies; and the defence of lawful correction needs to be repealed, with the aim of setting a new standard, as well as education rather than prosecution.